Accommodation outcomes for children of drug-misusing women. Issue 1 (13th December 2019) - Mitchell, Jennifer; Mactier, Helen
Abstract : Children of drug-misusing women are a vulnerable group. Data describing the pattern of accommodation placements are lacking. We investigated 10- to 12-year accommodation outcomes of children born to drug-misusing mothers at a single maternity hospital. 94% of mothers were prescribed maintenance methadone during pregnancy and at least 87% poly-drug used. Data were successfully matched for 132 children (29% of the original cohort of 450 babies). These children had a total of 291 placements (median 2 (range 1–6)), only 28.5% of which were with the birth parents. At 10–12 years, 54 (41%) were in the care of their parent(s). 83% (109/132) were discharged from the maternity hospital to their birth parents; 41% of these children (54/132) remained with their parents at 10–12 years. Of the 23 children not discharged from the maternity unit to their parents, 70% remain within the care system or have been adopted at 10–12 years of age.